PENYELIDIKAN ZONA AKUIFER DENGAN SURVEI PENDUGAAN GEOLISTRIK METODE SCHLUMBERGER STUDI KASUS DAERAH KECAMATAN KALIWUNGU DAN SEKITARNYA, KABUPATEN KENDAL, JAWA TENGAH - Enda Mora Nasution (Geological Engineering E-Journal, 2013)
Morphological differences research area affect to subsurface conditions. To determine subsurface conditions and hydrogeological conditions of the study area, then conducted research with geoelectric method.Geoelectric is a geophysical method used to determine geological subsurface conditions based on the variation of the resistivity of the rock types. Research area is located in Kaliwungu, Kendal Regency, Central Java. This area consisted by Damar Formation (QTd) and Alluvium Deposits (Qal). Damar Formation consisted by 3 lithological units, named : volcanic breccia, tuffaceous sandstones and conglomerates. Alluvium Deposit consisted by of sand, gravel, and pebble. The purpose of this study was to determine the zone and type of aquifer and direction of groundwater flow, based on Schlumberger geoelectrical method and groundwater level measurement on some shallow wells.This research used Schlumberger geoelectrical method. Geoelectric point in the study area totaled 15 points and as many as 16 MAT measurement data points are scattered in the study area. Data processing is done using software IPI2win to determine the actual value of resistivity and thickness of each layer and Surfer9 to determine groundwater flow direction.Based on the results of geoelectrical data processing on each lithological resistivity values, this research area formed by rock mudstone (≤ 10 Ωm), sandy mudstone (10-20 Ωm), sandstones (20-100 Ωm), and volcanic breccia (> 100 Ωm). Lithological type of the aquifer in research area is expected to be sandstones which have a good permeability and porosity. A geoelectrical section and correlation is made to determine the location, dimensions and types of aquifers that occur in the study area. The aquifer type identified by the correlation was uncofined aquifers, perched aquifer and confined aquifer. Groundwater flow direction based on the measurement of shallow wells tend to the north area of research.